Brief update of the new WHO classification for urothelial carcinoma. Issue 5 (15th September 2022) - Compérat, Eva; Wasinger, Gabriel; Oszwald, André; Shariat, Shahrokh F.
Abstract : Purpose of review: Six years after the release of the 4th edition of the WHO classification on male and genitourinary tumors in 2016, the upcoming 5th edition will be released in 2022. This review will discuss significant changes in the new WHO classification for urothelial carcinoma. Recent findings: Substantial progress has been made during the last 6 years, especially in the molecular definition of bladder cancer, but also in treatment approaches. The authors have incorporated these and other changes relating to surgical pathology and made relevant changes to provide a more logical and consistent structure in separating chapters. Summary: As the WHO bluebook is intended to be used worldwide, the authors believe that the impact of these changes will be considerable.